KONSEP PENERAPAN HUKUM KEWARISAN ISLAM NUSANTARA - Arifin, Muhammad Patri (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
Property is always become a medium to maintain relationships among human beings, both when alive and after death. When a person is alive, his or her possessions can be used as media to maintain good relations with others, as well as after death, abandoned property can still be used to maintain that relationship. One of them is through the division of inheritance.In Indonesia, although the provision of inheritance is still largely in accordance with the general provisions that have been formulated by the jurists, but for some people view the division of jurists irrelevant to the situation and conditions of Indonesia, so that some inheritance inheritance formulas are reconstructed as what has been formulated in Compilation of Islamic Law, there are even completely different due to the existing provisions.Hazairin, for example, looks to be the case of a person who dies unlawfully, both boy and girl. Hazarin distinguishes it in verses 12 and verse 176 surah an Nisa. In verse 12, you are not with a child, but with your father. Whereas in verse 176 the siblings are not with children and fathers. So for Hazairin there is no difference between siblings, having the same father and mother. Therefore, many of you at least in the two verses, should be sought in other relationships. Likewise, the legal reconstruction offered by Munawir Syadzali and Muhammad Syahrur has been widely considered in the formulation of his inheritance law in Indonesia, especially from academics and some judges in several Religious Courts taking into consideration in every decision.